Caroline Hall: Lessons from an expansion of upper secondary schooling - Hans Grönqvist; Caroline Hall (Institute for Labour Market Policy Evaluation (IFAU), 2011)
This paper studies effects of education policy on early fertility. We study a major educational reform in Sweden in which vocational tracks in upper secondary school were prolonged from two to three years and the curricula were made more academic. Our identification strategy takes advantage of cross-regional and cross-time variation in the implementation of a pilot scheme preceding the reform in which several municipalities evaluated the new policy. The empirical analysis draws on rich population micro data. We find that women who enrolled in the new program were significantly less likely to give birth early in life and that this effect is driven by women with higher opportunity costs of child rearing. There is however no statistically significant effect on men's fertility decisions. Our results suggest that the social benefits of changes in education policy may extend beyond those usually claimed.
Keywords: J13; I20; 330; Schooling reform; teenage childbearing; fertility; Bildungsreform; Allgemeinbildende Schule; Jugendliche; Mütter; Wirkungsanalyse; Schweden